Longitudinal dynamics and transformation of riverine dissolved organic matter from source to sea - Norbert Kamjunke; Peter Herzsprung; Wolf von Tümpling; Anna Matoušů; Petr Znachor; Tina Sanders; Holger Brix; Ingeborg Bussmann; Markus Weitere; Oliver J. Lechtenfeld (Water Research, 2026)

Identifying and addressing the components of extreme physical-oceanographical events for improved risk management in coastal systems - Eric P. Achterberg; Fabian Rackelmann; Ananya Ramesh; Jack O’Connor; Ovidio García-Oliva; Saranya Jayachandran; Viktoria Wichert; Xiangyu Li; Kaveh Purkiani; David M. Needham; Ingeborg Bussmann; Philipp Fischer; et al. (Frontiers in Marine Science, 2025)
Extreme physical-oceanographic events, such as marine heatwaves, fluvial floods, droughts and storm surges, have major impacts on local communities, economic sectors and ecosystems, and their frequency, intensity and duration increase due to climate change. There is a lack of understanding of the systemic drivers of extreme events as well as of their interconnected impacts on estuarine and coastal ecosystems. This knowledge is essential for assessing future impacts on ecosystem services and the local communities that depend on them, and to inform robust risk assessments and develop comprehensive risk management and adaptation strategies including early warning systems. Considering this, the German Alliance for Marine Research (DAM)-funded programme “ElbeXtreme” focuses on an integrated approach utilizing stakeholder engagement, data mining, experimental and field observations to develop novel observational and modelling approaches for assessing and monitoring risks in the Elbe estuary. The programme will deliver new insights into risks and impacts of extreme events in the estuarine system of the Elbe and the adjacent region of the North Sea (German Bight) to build a systemic risk understanding and support adaptation planning for local communities and ecosystems. Here we outline the rationale of the ElbeXtreme project and its planned activities, with the aim of stimulating national and international collaboration in tackling the urgent issue of marine and coastal risks.

Winter flood significantly changes salinity and nutrient export from land to sea - Ingeborg Bussmann; Holger Brix; Götz Flöser; Philipp F. Fischer; Saranya Jayachandran; Eric P. Achterberg; Kristine Carstens; Inga V. Kirstein; Tina Sanders; Björn Raupers; Yoana Voynova; Norbert Kamjunke (Frontiers in Marine Science, 2025)
Flood events caused by high rainfall can have profound biogeochemical impacts on riverine systems but also on the receiving coastal waters. The winter flood in Germany in December 2023/January 2024 affected the Elbe and Weser River systems. We obtained unique data during the peak of the flood and compared these with the monthly means from previous years (2018-2023). Hydrographic parameters and nutrients were determined by standard methods. Low salinity values were observed in the Elbe estuary and the adjacent German Bight (part of North Sea). At Helgoland the lowest average salinity was observed in January 2024 with 31.3 ± 0.5 compared to an average salinity of 32.7 ± 0.7 for the years 2016 to 2023. Nutrient loads (nitrate, phosphate) in the rivers showed a six- to 11-fold increase in the Elbe and Weser rivers compared to years without flood events. Enhanced concentrations of nitrate and silicate were found in the German Bight in January. Nutrients were diluted with North Sea waters, indicating a conservative behavior of nutrients in winter. Atypical prevailing meteorological conditions in January 2024, with predominantly easterly winds, potentially affect the dispersal of the river plume and the nutrients in the North Sea. In March 2024 the chlorophyll-a concentration strongly increased to 2.9 ± 1.8 µmol/L and was twice as high compared to only 1.5 ± 0.7 µmol/L observed in previous years. The observed intensified spring bloom in March in the German Bight near the island of Helgoland indicates the impacts of the flood-derived nutrient inputs three months after the flood event, as the timing of light and nutrient availability was optimal. It is assumed that seasonality and magnitude of flooding in the Elbe estuary and adjacent coastal region will change in future due to climate warming. Thus, the timing of light and nutrient availability will also change, with unconstrained impacts on primary producers and higher trophic levels.

Corrigendum to “Large-scale nutrient and carbon dynamics along the river-estuary-ocean continuum” [Sci. Total Environ. 890 (2023) 164421] - Norbert Kamjunke; Holger Brix; Götz Flöser; Ingeborg Bussmann; Claudia Schütze; Eric P. Achterberg; Uta Ködel; Philipp Fischer; Louise Rewrie; Tina Sanders; Johannes Pein; Benjamin Jacob; et al. (Science of The Total Environment, 2023)

Large-scale nutrient and carbon dynamics along the river-estuary-ocean continuum - Norbert Kamjunke; Holger Brix; Götz Flöser; Ingeborg Bussmann; Claudia Schütze; Eric P. Achterberg; Uta Ködel; Philipp Fischer; Louise Rewrie; Tina Sanders; Dietrich Borchardt; Markus Weitere (Science of The Total Environment, 2023)

Effects of Measuring Devices and Sampling Strategies on the Interpretation of Monitoring Data for Long-Term Trend Analysis - Philipp Fischer; Peter Dietrich; Eric P. Achterberg; Norbert Anselm; Holger Brix; Ingeborg Bussmann; Laura Eickelmann; Götz Flöser; Madlen Friedrich; Hendrik Rust; Claudia Schütze; Uta Koedel (Frontiers in Marine Science, 2021)
A thorough and reliable assessment of changes in sea surface water temperatures (SSWTs) is essential for understanding the effects of global warming on long-term trends in marine ecosystems and their communities. The first long-term temperature measurements were established almost a century ago, especially in coastal areas, and some of them are still in operation. However, while in earlier times these measurements were done by hand every day, current environmental long-term observation stations (ELTOS) are often fully automated and integrated in cabled underwater observatories (UWOs). With this new technology, year-round measurements became feasible even in remote or difficult to access areas, such as coastal areas of the Arctic Ocean in winter, where measurements were almost impossible just a decade ago. In this context, there is a question over what extent the sampling frequency and accuracy influence results in long-term monitoring approaches. In this paper, we address this with a combination of lab experiments on sensor accuracy and precision and a simulated sampling program with different sampling frequencies based on a continuous water temperature dataset from Svalbard, Arctic, from 2012 to 2017. Our laboratory experiments showed that temperature measurements with 12 different temperature sensor types at different price ranges all provided measurements accurate enough to resolve temperature changes over years on a level discussed in the literature when addressing climate change effects in coastal waters. However, the experiments also revealed that some sensors are more suitable for measuring absolute temperature changes over time, while others are more suitable for determining relative temperature changes. Our simulated sampling program in Svalbard coastal waters over 5 years revealed that the selection of a proper sampling frequency is most relevant for discriminating significant long-term temperature changes from random daily, seasonal, or interannual fluctuations. While hourly and daily sampling could deliver reliable, stable, and comparable results concerning temperature increases over time, weekly sampling was less able to reliably detect overall significant trends. With even lower sampling frequencies (monthly sampling), no significant temperature trend over time could be detected. Although the results were obtained for a specific site, they are transferable to other aquatic research questions and non-polar regions.

Detailed Patterns of Methane Distribution in the German Bight - Ingeborg Bussmann; Holger Brix; Götz Flöser; Uta Ködel; Philipp Fischer (Frontiers in Marine Science, 2021)
Although methane is a widely studied greenhouse gas, uncertainties remain with respect to the factors controlling its distribution and diffusive flux into the atmosphere, especially in highly dynamic coastal waters. In the southern North Sea, the Elbe and Weser rivers are two major tributaries contributing to the overall methane budget of the southern German Bight. In June 2019, we continuously measured methane and basic hydrographic parameters at a high temporal and spatial resolution (one measurement per minute every 200–300 m) on a transect between Cuxhaven and Helgoland. These measurements revealed that the overall driver of the coastal methane distribution is the dilution of riverine methane-rich water with methane-poor marine water. For both the Elbe and Weser, we determined an input concentration of 40–50 nmol/L compared to only 5 nmol/L in the marine area. Accordingly, we observed a comparatively steady dilution pattern of methane concentration toward the marine realm. Moreover, small-scale anomalous patterns with unexpectedly higher dissolved methane concentrations were discovered at certain sites and times. These patterns were associated with the highly significant correlations of methane with oxygen or turbidity. However, these local anomalies were not consistent over time (days, months). The calculated diffusive methane flux from the water into the atmosphere revealed local values approximately 3.5 times higher than background values (median of 36 and 128 μmol m –2 d –1 ). We evaluate that this occurred because of a combination of increasing wind speed and increasing methane concentration at those times and locations. Hence, our results demonstrate that improved temporal and spatial resolution of methane measurements can provide a more accurate estimation and, consequently, a more functional understanding of the temporal and spatial dynamics of the coastal methane flux.

Kelp deposition changes mineralization pathways and microbial communities in a sandy beach - Marit R. van Erk; Dimitri V. Meier; Timothy Ferdelman; Jens Harder; Ingeborg Bussmann; Dirk de Beer (Limnology and Oceanography, 2020)
We investigated the impact of kelp deposition on the geochemistry and microbial community composition of beach sands on the island of Helgoland (North Sea). The composition of the microbial community at a beach with regular kelp deposition appeared shaped by this regular input of organic material, as indicated by significantly higher proportions of aerobic degraders, fermenters, and sulfur cycling microorganisms. Rapid degradation of deposited kelp by this community leads to high levels of dissolved organic and inorganic carbon and nutrients, a lower pH and anoxia. Aerobic respiration, fermentation, Fe‐ and SO 4 2− reduction, and methanogenesis were strongly enhanced, with SO 4 2− reduction being the main process in kelp degradation. SO 4 2− reduction rates increased 20‐ to 25‐fold upon addition of kelp. The main route of electrons from kelp to SO 4 2− was not via CO and H 2 , as expected, but via organic fermentation products. O 2 supply by the tides was not sufficient and reduced intermediates escaped from the sediment with tidal water retraction. The resulting extremely high levels of free sulfide (>10 mmol L −1 ) lead to abundant filamentous growth of sulfur‐oxidizing bacteria largely composed of a rare O 2 ‐adapted Sulfurovum lacking the expected denitrification genes. Our results show that regular kelp deposition strongly enhances the thermodynamic disequilibrium in the beach sand habitat, leading to a dramatic enhancement of the sulfur cycle.

Methane dynamics in a large river: a case study of the Elbe River - Anna Matoušů; Martin Rulík; Michal Tušer; Adam Bednařík; Karel Šimek; Ingeborg Bussmann (Aquatic Sciences, 2019)

Methane distribution and methane oxidation in the water column of the Elbe estuary, Germany - Anna Matoušů; Roman Osudar; Karel Šimek; Ingeborg Bussmann (Aquatic Sciences, 2017)

Effects of climate change on methane emissions from seafloor sediments in the Arctic Ocean: A review - Rachael H. James; Philippe Bousquet; Ingeborg Bussmann; Matthias Haeckel; Rolf Kipfer; Ira Leifer; Helge Niemann; Ilia Ostrovsky; Jacek Piskozub; Gregor Rehder; Tina Treude; Lisa Vielstädte; et al. (Limnology and Oceanography, 2016)
Large quantities of methane are stored in hydrates and permafrost within shallow marine sediments in the Arctic Ocean. These reservoirs are highly sensitive to climate warming, but the fate of methane released from sediments is uncertain. Here, we review the principal physical and biogeochemical processes that regulate methane fluxes across the seabed, the fate of this methane in the water column, and potential for its release to the atmosphere. We find that, at present, fluxes of dissolved methane are significantly moderated by anaerobic and aerobic oxidation of methane. If methane fluxes increase then a greater proportion of methane will be transported by advection or in the gas phase, which reduces the efficiency of the methanotrophic sink. Higher freshwater discharge to Arctic shelf seas may increase stratification and inhibit transfer of methane gas to surface waters, although there is some evidence that increased stratification may lead to warming of sub‐pycnocline waters, increasing the potential for hydrate dissociation. Loss of sea‐ice is likely to increase wind speeds and sea‐air exchange of methane will consequently increase. Studies of the distribution and cycling of methane beneath and within sea ice are limited, but it seems likely that the sea‐air methane flux is higher during melting in seasonally ice‐covered regions. Our review reveals that increased observations around especially the anaerobic and aerobic oxidation of methane, bubble transport, and the effects of ice cover, are required to fully understand the linkages and feedback pathways between climate warming and release of methane from marine sediments.

Active pockmarks in a large lake (Lake Constance, Germany): Effects on methane distribution and turnover in the sediment - Ingeborg Bussmann; Stefan Schlömer; Michael Schlüter; Martin Wessels (Limnology and Oceanography, 2011)
In the eastern part of Lake Constance, the second largest prealpine lake in Europe, about 500 pockmarks (morphological depressions on the lake floor) were recently discovered. The diameters of these pockmarks are as large as 16 m, and about 24% of them continuously release methane in the form of visible bubbles. The isotopic composition of the escaping gas indicated that the methane was of biogenic origin and was predominantly produced by the CO 2 ‐reduction pathway. In shallow‐water pockmarks (9 m and 12 m), pore‐water analysis revealed increased methane concentrations of > 1100 µmol L −1 in the sediment. Diffusive methane fluxes and oxidation rates within these shallow pockmarks were much higher than in sediments outside pockmarks. An estimated methane ebullition into the water column of about 40 L h −1 per pockmark showed that methane ebullition is by far the dominant pathway of methane release from these shallow pockmarks. Meiofauna abundance and organic carbon contents of the sediment were also higher in the shallow pockmarks, but there were no differences in macrofauna. In a deep pockmark (80 m), even though bubble release was observed, the sediment inside the pockmark had almost the same methane concentrations and isotopic compositions as a site outside of the pockmark. At both sites, the shallow and deep pockmark act mainly as sedimentation traps, the emanating gas has only minor influence on the methane inventory of the sediments and, therefore, gas bubbles enter the water column essentially unaffected.

Distribution, morphology, and formation of pockmarks in Lake Constance, Germany - Martin Wessels; Ingeborg Bussmann; Stefan Schloemer; Michael Schlü ter; Volker Bö dere (Limnology and Oceanography, 2010)
Pockmarks are well known in the marine environment but almost unreported from limnic systems. In Lake Constance we investigated pockmarks near the mouth of the main tributary, Alpine Rhine River, using sediment cores and hydroacoustics (sidescan sonar, subbottom profiler, horizontal scanning sonar, multibeam echo sounder). The maximum dimension of an individual pockmark is about 16 m in diameter and 3‐4‐m deep, often with a round shape. Most pockmarks are located on top of morphological high points such as sediment waves or shoulders of old channels in front of the Alpine Rhine River. They are collapse structures formed when a reservoir of biogenic methane rapidly empties into the water column. Ebullition of gas very often was observed, indicating that biogenic methane still migrates toward pockmarks.